MAN AND MEANING: ОН THE LIFE AND WORK OF PROFESSOR KOLE JOVANOVSKI (1945-2020) (Годишен зборник на Филозофски факултет - Скопје, 2021)
On August 28, 2020, our philosophical community lost one of its most prominent representatives – Prof. Dr. Kole Jovanovski retired full professor at the Institute of Philosophy, Faculty of Philosophy, Ss. Cyril and Methodius University in Skopje. Professor Jovanovski left a very significant philosophical legacy, specifically in the fields of Philosophical Anthropology, Axiology, and Philosophical Terminology. His three most important professional books are related to these philosophical disciplines: Philosophical Anthropology [Филозофска антропологија] (2000), Philosophical Dictionary [Филозофски речник] (2002) and The Problem of Meaning [Проблемот на смислата] (2005).